Distributed attitude synchronization control for multiple flexible spacecraft without modal variable measurement. (22nd March 2018) - Wang, Qishao; Duan, Zhisheng; Lv, Yuezu
Summary: This paper solves the attitude synchronization and tracking problem for a group of flexible spacecraft without flexible‐mode variable measurement. The spacecraft formation is studied in a leader‐following synchronization scheme with a dynamic virtual leader. With the application of adaptive sliding‐mode control technique, a distributed modified Rodriguez parameters‐based dynamic controller is proposed for flexible spacecraft without requiring modal variable measurement. It is proved that the attitude synchronization and tracking can be achieved asymptotically under the control strategy through the Lyapunov's stability analysis. Furthermore, a distributed robust continuous control algorithm is designed to guarantee the ultimate boundedness of both the attitude tracking error and the modal variable observation error when bounded external disturbances exist. Some numerical simulation examples for multiple flexible spacecraft formation are given to demonstrate the effectiveness of the proposed method.